Thomas Kuhn, kamene a fyzikálne zákony - Rorty, Richard (Organon F, 1997)
Although many philosophers do not consider Thomas Kuhn to be a great philosopher, there are at least two reasons to do so. First, he helped to remap our culture and created for it a new structural plan, and second even without being educated in philosophy his work bears an important metaphilosophical message. I took his work and applied consequences on the field of philosophy which helped me to view our culture not as an epistemological and ontological hierarchy reaching from formal sciences down to rhetoric, but as a spectrum of viewpoints with rigidity of norms on one end and constant change on the other. There are still those who think Kuhn should not be taken seriously. Among them there are both analytic philosophers and natural scientists. Steven Weinberg serves as a great example. He believes that by virtue of his participation in the actual process of making physics he knows all the problems of philosophy of his discipline. He uses terms which philosophers were deciphering for a long time without any contemplation over their meaning. Kuhn is one of the greatest philosophers of the 20th century and although he was afraid to articulate all consequences of his revolutionary work, he did a great job in showing us that the privileged position science has in our culture in not entirely justified.